Comform:Exposing the truth about common core and public education - Beck, Glenn, (Control series, 2014)
Bestselling author and popular radio and television host Glenn Beck considers the hot-button issue of education in the US, exposing the weaknesses of the Common Core school curriculum and examining why liberal solutions fail. --